Political opportunity structure under the administration of President Benigno S. Aquino III: A case study of a social movement of informal settler families in the Philippines - San Pedro-Raymundo, Alicia (Quezon City Asian Center, University of the Philippines Diliman, 2022)
The study investigates how and why a movement of informal settler families in the Philippines engaged actively with the administration of President Benigno S. Aquino III in 2010 to 2016. The social movement, Kilos Maralita, originated from the Left movement in the country and was born out of the struggle for the ouster of former President Gloria Macapagal-Arroyo from 2005-2009. It had historically shun participation in invited spaces because it always expected an elite state to work against the interest of the poor. The Aquino Administration, while it had liberal tendencies, was still dominated by political leaders from traditional elite political clans who are generally wary and hostile to the Left and other challengers.

How and why a Left social movement entered into a collaborative partnership with a predominantly elite state and included in its repertoire of contention more assimilative forms, while still launching confrontational actions is attributed in this study to the nature of political environment which prevailed in the Philippines from mid-2010 to mid-2016. Guided by the political opportunity structure theory, this study illustrates the elements of that political environment, how they influcend the conduct of an urban poor social movement, and the outcomes of the social movement's actions.
Includes bibliographical references
Thesis (Master of Arts in Philippine Studies)
Keywords: Aquino, Benigno Simeon Cojuangco .; Urban poor -- Case studies -- Philippines; Philippines -- Politics and government; Philippines -- Economic conditions